The Financial Aspect of Non_Governmental Organizations: - Tatjana Stanimirović (Central European Public Administration Review)
Aim: Non-governmental organizations as part of the third sector have become an important factor in the public life of modern countries. This emerging wave can be noticed especially in the South-East Europe in the transition period. In this context, the aim of the paper is to analyse the financial aspect of the NGOs' business model, exposing cumulative data for the last 11 years in Slovenia. Design/Methodology/Approach: Based on the financial data obtained, the paper reveals the structure of financial resources of Slovenian NGOs, delving into total amounts, as well as trends of changes for specific resources.  Using descriptive methodology, it focuses mainly on dissection of resources provided from public finance. Findings: The results show that in 2019 NGOs in Slovenia achieved almost 1 billion euro of total revenues, after they were increasing rapidly in the hole observed period (2009-2019). As far as resources obtained from public finances are concerned, the amount is higher at governmental level provided by ministries then at the local level received from municipalities, what has not been the case before year 2019. Practical implications:  The challenge for further research is the in-depth study of Slovenian NGOs’ financial strategy focusing on the challenge of bidirectional financing as well as analysis of public services provided by NGOs at the moment compared to services needed in the future. Originality/value: The paper is the pioneer attempt among scientific papers to analyse the financing of NGOs in Slovenia.